Budaya Organisasi dan Inovasi Pelayanan Publik: Mengapa Inovasi Sulit Bertahan - Sri Yulianty Mozin; Sesilia U. Taidi; Marsha Oktaviani Sila; Fija Ahaya (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the relationship between organizational culture and the sustainability of public service innovation within government bureaucracy. Although many public service innovations show positive results in the initial stages, many do not sustain in the long term. This indicates the presence of fundamental factors affecting innovation sustainability, one of which is organizational culture. Organizational culture plays a role in shaping the behavior, values, and work methods of civil servants in providing services to the public. This study aims to analyze the role of organizational culture in supporting or hindering the sustainability of public service innovations. Using a Systematic Literature Review (SLR) approach, this study analyzes 20 relevant scientific articles from 2002 to 2025. The results indicate that hierarchical, rigid, and administratively-oriented organizational cultures hinder innovation sustainability. Other factors such as low leadership support, limited incentives, and resistance to change also strengthen these barriers. Conversely, an open, collaborative, and adaptive organizational culture to change enhances the likelihood of innovation sustainability. In conclusion, the success of public service innovations is greatly influenced by the organizational culture underlying the behavior of civil servants. Therefore, transforming organizational culture to be more innovative and adaptive is a strategic step to strengthen the sustainability of innovation.